Development of protective materials based on glass- and slag-containing portland cement structures - Бондаренко, Ольга Петровна; Гузий, Сергей Григорьевич; Захарченко, Екатерина Дмитриевна; Новоселенко, Елизавета Дмитриевна (Eastern-European Journal of Enterprise Technologies, 2015)
The effect of the glass powder of the broken container glass on the strength and corrosion resistance of protective materials based on the slag-containing Portland cement is investigated. Using the three-factor simplex-centroid experimental design, the optimization of structures of protective materials, bounded on the axis X1 by the content of granulated blast-furnace slag (GBFS) of 25–50 %, on the axis X2 – the amount of glass powder (GP) of 5–10 %, on the axis X3 – the changes in W/C of 0.24–0.3 is carried out. As a result, the optimum structure of the protective material comprising 40% of GBFS (X1 factor), 10 % of GP (X2 factor) at W/C=0.3 (X3 factor) is obtained. The material is characterized by a flexural strength of 6.5-8.1 MPa in the range of 2–28 days and the resistance coefficient of 1.38–2.1 after curing samples in corrosive environments for 60 days. A slight loosening of the surface layer of the protective material of the optimum structure in the environment of 5 % sodium sulfate solution due to the formation of the corrosion product – calcium sulfate is observed. The macrostructure of the stone chip of the investigated structure aged for 60 days in solutions of 5 % sodium chloride and sulfate was not affected. The approbation of the protective material of the optimum structure to determine its resistance to aggressive influences of an urban environment when restoring the damaged section of the reinforced concrete slab on the "Kyivska Rusanivka" railway halt is performed. It is shown that after 7 days of hardening in difficult weather conditions, no changes on the surface of the developed protective material, as well as gaps between the material and the concrete base were observed. The data obtained allow to recommend the developed material for restoring and protecting concrete and reinforced concrete structures of transport facilities in an aggressive urban environment, and also for improving the ecology of the region by recycling of broken container glass.